2020
DOI: 10.3389/feduc.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Skills Assessment in Digital Crisis Management Training for the Safety Domain: Developing an Unobtrusive Method

Abstract: This study aims to develop an unobtrusive assessment method for information literacy in the context of crisis management decision making in a digital serious game. The goal is to only employ in-game indicators to assess the players' skill level on different facets of information literacy. In crisis management decision making it is crucial to combine an intuitive approach to decision making, build up by experience, with an analytical approach to decision making, taking into account contextual information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…They constructed a test of 28 situational judgment tasks that provided students with a scenario description and several possible procedures to solve the scenario and requested them to rate each procedure according to its usefulness. Also worth mentioning is the serious game of Steinrücke et al (2020). They measured information literacy by classifying the in-game behavior of individuals playing a crisis situation manager game.…”
Section: Assessment Approachesmentioning
confidence: 99%
“…They constructed a test of 28 situational judgment tasks that provided students with a scenario description and several possible procedures to solve the scenario and requested them to rate each procedure according to its usefulness. Also worth mentioning is the serious game of Steinrücke et al (2020). They measured information literacy by classifying the in-game behavior of individuals playing a crisis situation manager game.…”
Section: Assessment Approachesmentioning
confidence: 99%
“…For example, van de Ven et al (2014) used a former version of the Dilemma Game to provide insight into different leadership styles. In a more recent study, Steinrücke et al (2020) discuss, that the Dilemma Game can be used to train and assess information literacy. The authors found a clear correlation between styles of in-game behavior and performance on specific facets of information literacy.…”
Section: Methods the Dilemma Gamementioning
confidence: 99%
“…Given the close interaction between information and its context, training IL in practical domains as crisis management decision-making is a complex task to achieve efficiently (see Steinrücke et al, 2020). Training sessions in crisis management decision-making should be realistic, which means that they should be designed similar to real life crisis situations.…”
Section: Information Literacy Training In Crisis Management Practicementioning
confidence: 99%
See 2 more Smart Citations